STUDI USIA PEKERJA DAN KEPEDULIAN TERHADAP BAHAYA DI LINGKUNGAN PROYEK KONSTRUKSI - Jonathan Saputra; Suripto #; Farah Zul Faykal (Politeknik Negeri Jakarta, 2022)
The development of the construction industry shows increasingly stringent and complex challenges. The high number of work accidents in Indonesia is caused by several reasons, one of which is the lack of workers' awareness of the dangers contained in project work. This gives a signal that young people have the potential to lack awareness of safe behavior. This study aims to determine whether young workers are one of the causes of work accidents in the construction environment, the level of workers' awareness of hazards, and the dominant factors that affect the level of workers' awareness of hazards in the construction environment. Factors that affect the level of worker concern about hazards in the construction environment include the availability of complete PPE, strict sanctions against workers who violate SHE regulations, and the availability of a special unit that manages SHE. The method to analyze the data was one-sample t-test. From the research result, young workers still become one of the factors of work accidents, and the level of awareness of young workers towards hazards in the construction environment is still minimal or low. The dominant factor that affects the level of concern for workers to hazards in the construction environment is the availability of a special unit that manages SHE. Keywords: Work accident, Young worker, Level of awareness of worker.